Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay (Studi Empiris Pada Perusahan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Salsabilla, Adelia; , Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2016)
ABSTRACT Time difference between financial statement and auditing opinion date indicates the amount oftime needed in auditing settlement period. This condition can affect the punctuation of theinformation published and will influence market reaction towards the lengthy information. It willalso the level of uncertainty based on the published information in the auditor's financialstatement in which containing company's profit information. This study aims to measure thefactors which affect audit delay. They are total asset, debt to asset ratio,profitability, auditor's opinion, and auditor's reputation.The population of the study is the manufactured companies registered in the Indonesia StockExchange in the period of 2012-2014. Sampling technique employed in this study is the purposivesampling with the total sample of 168 companies. The data analysis uses multiple regressions.The result of the study shows that the total asset, profitability and auditor's reputation have significant influencetowards audit delay. On the other hand, debt to asset ratio and auditor's opiniondo not have any influence towards audit delay. Key words: Audit Delay, the size of the company, operation debt to asset ratio,profitability, auditor's opinion, auditor's reputation.